Effectiveness of internal audit function as corporate governance mechanism in Tanzanian public sector: The case of internal auditor general’s division - Kimaro, Godlove (Mzumbe University, 2024)
A Dissertation Submitted in Partial Fulfilment of the Requirements for Award of the Degree of Master of Science in Accountancy and Finance (MSc A& F) of Mzumbe University